Depth extraction in 3D holoscopic images - Medeiros, João Diogo Gameiro (2019)
Holoscopy is a technology that comes as an alternative to traditional methods of capturing images and viewing 3D content. A light field camera can be used for the capture process, which allows the storage of information regarding the direction all light rays, unlike the traditional cameras. With the saved information it is possible to estimate a depth map that can be used for areas such as robotic navigation or medicine. This dissertation proposes to improve an existing depth estimation algorithm by developing new processing mechanisms which provide a dynamic balancing between computational speed and precision. All proposed solutions were implemented using CPU parallelization in order to reduce the computing time. For the proposed algorithms, qualitative tests were performed using the Mean Absolute Error (MAE), Root Mean Square Error (RMSE), and Structural Similarity Index Method (SSIM). A comparative analysis between the processing times of the proposed algorithms and the original solutions was also performed. The achieved results were quite satisfactory since there was a significant decrease in processing times for any of the proposed solutions without the accuracy estimate being substantially affected.